Estimating Risk for Future Intracranial, Fully Implanted, Modular Neuroprosthetic Systems: A Systematic Review of Hardware Complications in Clinical Deep Brain Stimulation and Experimental Human Intracortical Arrays. Issue 4 (20th November 2019) - Bullard, Autumn J.; Hutchison, Brianna C.; Lee, Jiseon; Chestek, Cynthia A.; Patil, Parag G.
Abstract : Objective: A new age of neuromodulation is emerging: one of restorative neuroengineering and neuroprosthetics. As novel device systems move toward regulatory evaluation and clinical trials, a critical need arises for evidence‐based identification of potential sources of hardware‐related complications to assist in clinical trial design and mitigation of potential risk. Materials and Methods: The objective of this systematic review is to provide a detailed safety analysis for future intracranial, fully implanted, modular neuroprosthetic systems. To achieve this aim, we conducted an evidence‐based analysis of hardware complications for the most established clinical intracranial modular system, deep brain stimulation (DBS), as well as the most widely used intracranial human experimental system, the silicon‐based (Utah) array. Results: Of 2328 publications identified, 240 articles met the inclusion criteria and were reviewed for DBS hardware complications. The most reported adverse events were infection (4.57%), internal pulse generator malfunction (3.25%), hemorrhage (2.86%), lead migration (2.58%), lead fracture (2.56%), skin erosion (2.22%), and extension cable malfunction (1.63%). Of 433 publications identified, 76 articles met the inclusion criteria and were reviewed for Utah array complications. Of 48 human subjects implanted with the Utah array, 18 have chronic implants. Few specific complications are described in the literature; hence, implant duration served as a lower bound for complication‐free operation. The longest reported duration of a person with a Utah array implant is 1975 days (~5.4 years). Conclusions: Through systematic review of the clinical and human‐trial literature, our study provides the most comprehensive safety review to date of DBS hardware and human neuroprosthetic research using the Utah array. The evidence‐based analysis serves as an important reference for investigators seeking to identify hardware‐related safety data, a necessity to meet regulatory requirements and to design clinical trials for future intracranial, fully implanted, modular neuroprosthetic systems.